PENGGUNAAN MEDIA GAMBAR UNTUK MENINGKATKAN MINAT BELAJAR PKN SISWA KELAS III SD NEGERI 006 PAGARAN TAPAH DARUSSALAM - Karsih, Karsih (Aksara Public, 2017)
This research is motivated by the lack of interest in learning civics third grade students of SD Negeri 006 Pagaran Tapah Darussalam. This study aims to determine the appropriate action in the use of media images in order to increase interest in studying Civics Grade III Elementary School 006 Pagaran Tapah Darussalam, held for 1 month. Subject research is all students of Class III SD Negeri 006 Pagaran Tapah Darussalam which is the subject of this study is 32 students consisting of 15 students lak male and 17 female students. Form of research is classroom action research. The research instrument consists of instruments and instrument performance data collection activity observation sheet form teacher and student activity. Based on specified performance indicators can be concluded that the use of media images in increasing student interest in the subject class III civic education SD Negeri 006 Pagaran Tapah Darussalam is successful from the first cycle of 51.3% to 79.4% in cycle II. The successful use of media images on this second cycle due to the teacher to modify both forms of media images of size or color is more attractive. This situation is more attracted the attention of students in expressing an idea or opinion presented to the media image that has not been presented by the teacher in the learning process.